Binding of inferred germline precursors of broadly neutralizing HIV-1 antibodies to native-like envelope trimers - Sliepen, Kwinten (Virology, 2015)
HIV-1 envelope glycoproteins (Env) and Env-based immunogens usually do not interact efficiently with the inferred germline precursors of known broadly neutralizing antibodies (bNAbs). This deficiency may be one reason why Env and Env-based immunogens are not efficient at inducing bNAbs. We evaluated the binding of 15 inferred germline precursors of bNAbs directed to different epitope clusters to three soluble native-like SOSIP.664 Env trimers. We found that native-like SOSIP.664 trimers bind to some inferred germline precursors of bNAbs, particularly ones involving the V1/V2 loops at the apex of the trimer. The data imply that native-like SOSIP.664 trimers will be an appropriate platform for structure-guided design improvements intended to create immunogens able to target the germline precursors of bNAbs.